2017
DOI: 10.1002/2017ef000632
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of Sustainable Development Goal (SDG) Interactions

Abstract: Sustainable development goals (SDGs) have set the 2030 agenda to transform our world by tackling multiple challenges humankind is facing to ensure well‐being, economic prosperity, and environmental protection. In contrast to conventional development agendas focusing on a restricted set of dimensions, the SDGs provide a holistic and multidimensional view on development. Hence, interactions among the SDGs may cause diverging results. To analyze the SDG interactions we systematize the identification of synergies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
710
6
30

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,141 publications
(926 citation statements)
references
References 36 publications
28
710
6
30
Order By: Relevance
“…Nevertheless, checking against data could help to improve the model by identifying decisive additional factors and including them. Another relevant application of data from correlations (Pradhan et al, 2017) would be to build a model based on the strengths of identified correlations. However, this would not be insightful unless the modeler checks for redundancies from existing indirect connections and addresses other common fallacies relevant to attributing correlation with causation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, checking against data could help to improve the model by identifying decisive additional factors and including them. Another relevant application of data from correlations (Pradhan et al, 2017) would be to build a model based on the strengths of identified correlations. However, this would not be insightful unless the modeler checks for redundancies from existing indirect connections and addresses other common fallacies relevant to attributing correlation with causation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Pradhan et al (2017) in their approach point out correlations between the SDGs' indicators that contradict the ICSU's results. The possibility thus exists that, as they themselves noted, "…correlation does not imply causality…" and "…while the mechanisms generating synergies and trade-offs remain elusive in our analysis, we complement approaches using process-based models by investigating the entire option space in which synergies and trade-offs emerge…".…”
Section: Connecting the 17 Sdgs And Their 169 Targetsmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on the results of driving force analysis of ELPL change, the Sustainable Development Goals (e.g., economic growth and urbanization) have synergetic or trade-off relationship with the ELPL change. The trade-offs directly affect the status of regional eco-environment and food production, which constitute obstacles in achieving the SDGs, need to be negotiated and made structurally nonobstructive by deep changes in the current strategies [46].…”
Section: Impacts Of Elpl Changes On Sustainable Developmentmentioning
confidence: 99%
“…These factors were significantly positively correlated with the change of LL and PLL but negatively correlated with the change of EPL and PEL. Referring to the study of Pradhan et al (2017) to analyze the sustainable development goal (SDG) interactions [46,47], the positive and negative correlations between socioeconomic factors and the changes of ELPL can be classified as synergy and trade-off. The economic development and the increase of population, consumption, fiscal revenue, investment and income have a synergetic relationship with the increasing of LL and PLL, whereas trade-offs relationship with EPL and PEL.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%